The woven narratives : weaving climate change science, ecologies and mātauranga Māori through spatial constructs : an exegesis presented in partial fulfilment of the requirements for the degree of Masters of Design at Massey University, Wellington, New Zealand - Abbott, Mercia (Massey University, 2021)
The threat of sea level rise and climate change is inevitable and happening. Indigenous coastal farming communities in particular, are at risk from coastal erosion, storm surges, groundwater inundation by salt water and extreme weather and flooding events. Many of these communities are slow to act due to a disconnect in synthesising western and indigenous knowledge systems. We are constantly told about the effects of climate change and there has been a lot of research compiled, data collected, collated and measured. The problem is it can be difficult to engage with science, due to statistics and figures that can feel psychologically distant and impersonal. This results in a lack of clear communication and difficulty for our communities to actively engage in and fully implement change. This thesis aims to address this disjuncture by weaving western science with mātauranga Māori knowledge systems to produce meaningful mahi that enhances cultural understanding, taonga species and environmental wellbeing within the Kuku rohe, in Horowhenua, south west coast of Te Ika-a-Māui, Aotearoa. A way of overcoming disconnection is to use Spatial design as a generative tool through the use of innovative 3D spatial modelling technologies, to construct embodied narratives that communicate the importance of climate change and mātauranga Māori. Spatial design does this by using immersive and atmospheric environments that enable people to connect to uncertain outcomes of climate change and to communicate people’s experiences, knowledge, stories and lives alongside scientific data. This enables a form of communication that can be understood and felt in terms of both the tangible and intangible, connecting people and data through this contact zone of shared suffering due to climate change. This mahi employed Kaupapa Māori methodologies such as: Whakapapa defined as genealogical systems that explain the intricate relationships between humans, cosmologies and everything within nature. Wānanga or embodied workshops took place with kaumātua, kaitiaki, iwi, hapū and researchers in climate change science and ecosystem services. Hīkoi involved walking, talking, meeting of minds, bodies and hearts to experience the land. Kōrero tuku iho is another method defined as past, present and future, oral narratives and pūrākau which are stories that shape our understanding, knowledge, values and worldviews of distinct places. These kaupapa Māori methodologies are crucial for effective engagement and have resulted in creating a combined richness of shared knowledge and expertise. Each method provided first-hand experience of ecological concerns and loss of natural integrity, mauri and wellbeing, integrating embodied knowledge, climate change science and data. Collectively, they offered culturally sensitive information for more responsive collaborations, with spatial design as the tool that weaves these knowledge systems together. This engagement sets up a potential model for other coastal communities to aid them in understanding today’s unfolding climate crisis and assist in implementing place-based change.
Keywords: Māori Masters Thesis; 451110 Te whakaharatau me te whakahaere hoahoa o te Māori (Māori design practice and management)